A taxonomic revision of Lemna sect. Uninerves (Lemnaceae) - Hoàng, Thị Như Phương (2022)
Lemna sect. Uninerves Hegelm. consists of three species, Lemna minuta Kunth (synonym L. minuscula), L. valdiviana Phil. and L. yungensis Landolt. Lemna yungensis was discovered growing on rocks in the Yungas in Bolivia by E. Landolt and was described just 20 years ago. In the original description, Landolt reported that this species is closely related to L. valdiviana and that it is difficult to distinguish the three species on a morphological basis. Therefore, the taxonomic position and status of L. yungensis remained controversial. Here, we carried out a detailed taxonomic study, integrating approaches that include quantitative morphometry, metabolomic profiling by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOFMS) as well as molecular genetic analysis using amplified fragment length polymorphism (AFLP), and barcoding of plastidic sequences. We also investigated genome sizes of clones of the three species. Whereas L. minuta can easily be differentiated from L. valdiviana and L. yungensis, it was not possible to distinguish L. valdiviana from L. yungensis with any of the methods used. These data imply that L. yungensis is identical to L. valdiviana. Thus, the name L. yungensis should be synonymised with the name L. valdiviana, since this is the older name.